STRATEGI PENGEMBANGAN FASILITAS WISATA DI OBJEK WISATA PANTAI PASIR JAMBAK PADANG - ,, Ridnaldi (journal of residu, 2019)
This research is motivated by a lack of facilities in the tourist attraction of Padang's Pasir Jambak Beach. This research is a descriptive study with a qualitative data approach using the survey method. Data collection techniques are carried out using the method of observation, interviews, and documentation. In this study using Snow-Ball Sampling involving informants, namely: one employee of the Tourism and Culture Office of the City of Padang, three people and three tourists. Data is analyzed in a reduction that is summarizing, selecting and focusing on important things, and analyzing the data obtained on the problem under study.The results of this study indicate that: 1) The strength of the development of facilities at the Pasir Jambak Beach tourist attraction is the availability of potential land, and the scenery of the beach that is still beautiful and cool. 2) Weaknesses in developing facilities at Pasir Jambak Beach are limited budgets, lack of initiative in developing facilities at tourist attractions, and some lands are still community property and lack of promotion of tourist objects. 3) Opportunities for developing facilities at coastal attractions Pasir Jambak is the presence of outside and private investors, government contributions, availability of human resources, and the availability of media that can be used as tourism promotion facilities. 4) Threats from the development of facilities in the Pasir Jambak Beach tourist attraction are still low community participation, the difficulty of community acceptance of cultural differences, unhealthy competition and the difficulty in managing new business permits.The strategy for developing facilities at Pasir Jambak Beach attractions is in the form of: a) Utilizing and developing the potential of existing land in tourism objects, b) Increasing cooperation between local governments, the central government, relevant agencies, communities, and investors in developing facilities at tourist attractions, c) Conducted promotional efforts by highlighting tourism objects and uniqueness, d) The government allocates funds for the development of facilities, e) Improves the quality of products in tourism objects.